THE IMPACT OF READING SHORT STORIES ON STUDENTS’ WRITING STYLE - Adizova Madina Ilyosovna; Diana Roʻzmetova (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract The reading of short stories is one of the most important aspects of students’ writing skills and styles development. Reading and writing have been related as one of the most important issues in language learning and teaching for a long time. Short stories reading brings learners into direct contact with the language, helps them to discover the basic elements of the story, makes their vocabulary larger, and their ability to communicate in a creative and logical way is a lot better. The paper deals with the topic of how reading short stories impacts the development of writing style with vocabulary enrichment, syntactic awareness, creativity, and narrative organization being the main focus. The study also suggests various practical ways in which the teaching of stories can be incorporated into writing classes for the sake of increasing the learners’ fluency, originality, and confidence.